Customer Purchasing Decision That Are Influenced by Online Customer Reviews, Online Customer Ratings, And Customer Trust in The Shopee E-Commerce in Pekanbaru - Arrauda Dhiza; Alvi Furwanti Alwie; Syapsan Syapsan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
This study aims to test and analyze test and analyze the influence of online customer reviews, online customer ratings, and customer trust on customer purchasing decisions on Shopee e-commerce. In the e-commerce system, buyers cannot try the product directly, so the existence of online customer reviews and online customer ratings will be a tool to measure product quality, delivery time, service, and others. Seeing the opportunity to develop this study, the researcher added a customer trust variable as a moderating variable that was not found in previous studies, the researcher believes that customer trust can strengthen or weaken online customer reviews and online customer ratings both directly and indirectly on purchasing decisions. The population in this study were Pekanbaru city residents who actively used the e-commerce shopee and were 20-40 years old because they were considered mature in purchasing decisions. The sample in this study was 166 people. The sample method used the purposive sampling method. The data used in this study were primary data and secondary data, while the data collection technique used a questionnaire. The model used in this study is a causality model or influence relationship. To test the hypothesis that will be proposed in this study, the analysis technique used is SEM or Structural Equation Modeling which is operated through the SmartPLS 3.2.8 program. The results of the study indicate that online customer reviews have an effect on purchasing decisions. Online customer ratings have an effect on purchasing decisions. This shows that online customer ratings have an important role in increasing purchasing decisions. Customer trust moderates the effect of online customer reviews on purchasing decisions. This shows that trust has an important role in strengthening the effect of online customer reviews on purchasing decisions. Customer trust moderates the effect of online customer ratings on purchasing decisions. This shows that trust has an important role in strengthening the effect of online customer ratings on purchasing decisions.